Gay Self Concept and Presentation at Art Activities Group in Padang City - Handayani, Susi; Sari, Kumala; Syahrul, Syahrul (Journal of Social Studies Arts and Humanities (JSSAH), 2024)
This study wants to know about gay self-concept and how self-presentation is displayed when in a family environment. Gay Padang City. The method used is a qualitative research method using dramaturgical theory. Dramaturgy by Erving Goffman, is a theory that explains that humans live life like a drama by playing various roles when interacting with other people. The research informants consisted of two people who claimed to be gay, namely Carlo and Fredo. The research method used is descriptive qualitative. The research data were collected by means of observation, interviews, and documentation. Researchers also interviewed their friends in the arts group who were also gay. The results showed that the two informants had a self-concept as gay who identified himself as a person with deviant sexual behavior. The front stage in the family environment shows that both informants limit their interactions and control their attitudes because they do not want their families to know that they are gay. Meanwhile, on the front stage of the gay fellow group in art activities, the two informants were more free to express themselves and were not ashamed to show their identity as gay. Both informants consciously manage the impression of the self-presentation that is done.